In-Shoe Loading in Rearfoot and Non-Rearfoot Strikers during Running Using Minimalist Footwear - Kernozek, T. W.; Meardon, S.; Vannatta, C. N. (International Journal of Sports Medicine, 2014)
Recent trends promote a “barefoot” running style to reduce injury. “Minimalist” shoes are designed to mimic the barefoot running with some foot protection. However, it is unknown how “minimalist” shoes alter plantar loading. Our purpose was to compare plantar loads between rearfoot strikers and non-rearfoot strikers after 4 weeks of running in minimalist footwear. 30 females were provided Vibram® Bikila shoes and instructed to gradually transition to running in these shoes. Plantar loading was measured using an in-shoe pressure sensor after the 4 weeks. Multivariate analysis was performed to detect differences in loading between rearfoot and non-rearfoot strikers in different plantar regions. Differences in plantar loading occurred between foot strike patterns running in minimalist footwear. Pressure and force variables were greater in the metatarsals and lower in the heel region in non-rearfoot strikers. Peak pressure for the whole foot was greater in non-rearfoot strikers while no difference was observed in maximum force or contact time for the whole foot between strike types. Allowing time for accommodation and adaptation to different stresses on the foot may be warranted when using minimalist footwear depending on foot strike pattern of the runner.
Keywords: pressure; biomechanics; kinetics; metatarsal; stress